The Influence Of School Environment On Student Learning Outcomes In Pancasila Education (PP) Class IV-A - Pristin Aprianto Simamora; Lisbet Sihombing; Janwar Tambunan (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the influence of the school environment on Pancasila education in Class IV-A UPTD SD NEGERI 122371 PEMATANGSIANTAR. This type of research is quantitative research. The population in this study were all students at SD 122371 Pematangsiantar totaling 16 students. Sampling was carried out using a saturated sampling technique by taking 2 classes, namely class IV-A and IV-B, into classes by applying the influence of the school environment on student learning outcomes in Pancasila Education (PP) Class IV-A. The research data were collected using a questionnaire of 35 questions, the questions have been validated and are included in the valid category. 90.38 so that the influence of the school environment on student learning outcomes in Pancasila Education (PP) CLASS IV-A. Data analysis was carried out using normality tests and hypothesis tests/t-tests. For the normality test using the Kolmogorov-Smirnov Test to determine whether the data in this study is normally distributed or not using the SPSS version 21 statistical program. The sig pre-test and post-test class values meet the sig value of 0.80> 0.05 so that the data can be declared normally distributed. In the normality test using the one-sample Kolmogorov Smirnov test, significant results were obtained> 0.05 so that the normality test was normally distributed. In the homogeneity test, it can be seen from the significance value of 0.39 which indicates that the significance value is greater than 0.05 so that there is homogeneity between the School Environment and Student Learning Outcomes. The validity test can be seen that 32 questionnaires are declared valid, and 3 questionnaires are invalid. And it is concluded that r_count is greater than r_table ((r_count from each statement item above> 0.05)). For example, in statement number 34 (0.80> 0.05), the questionnaire conducted by the researcher in using the data is valid. Based on the results of the validation calculation with 35 questionnaire statement items, the number of respondents was 16 students where the significance level was 5% and Rtable 0.05 where it is known that if Rcount > Rtable l. Not all statement items are said to be valid, it can be seen that from 35 statements there are 3 invalid statements and 32 valid statements, so it can be used as a data collection tool, it can be seen that all questions given to students are declared reliable, because the Croabach's Alpha value> 0.39 is 35